Legal Protection of the Right of Housewives to the Risk of HIV / AIDS in the city of Semarang - Ratih Sukmo W; Agnes Widanti; Hadi Sulistyanto (Universitas Katolik Soegijapranata Semarang, 2019)
One of the health issues in the world today remaining to be a trending topic is about HIV/AIDS. The incidence number of HIV/AIDS is increasing every year, including that it is experienced by housewives. Meanwhile, the housewives had the right to be free from sexually transmitted diseases, especially HIV/AIDS. The purpose of this study was to know the form of legal protection and the role of the government in fulfilling the housewives’ rights against the risk of HIV/AIDS transmission.This study used a socio-legal approach and a descriptive-analytical specification. The interviewees or informants consisted of 5 housewives suffering from positive HIV/AIDS and it was also done to 5 housewives who were negative but their husbands were positively suffering from HIV/AIDS. Meanwhile, the resource persons were from the Semarang City Health Office, the AIDS Prevention Commission, and the “Peduli Kasih” Foundation. The housewives’ rights of being free from sexually transmitted diseases had been regulated in several regulations but the implementation had not been evenly distributed throughout the city of Semarang. The factors that caused an increase in the number of housewives getting HIV/AIDS were socio-cultural and economic vulnerabilities, lack knowledge and information about HIV/AIDS, lack of awareness of the risky infected couples to check themselves to hospitals, discrimination treatment against HIV/AIDS sufferers and lack of health facilities. The role of the family was very influential for the housewives suffering from HIV/AIDS to survive. The supports that could be given to the housewives were emotional, appreciation, material, information, and socializing supports.